Investigation on steady-state temperature field by a novel laminated tooth for multi-tooth in harmonic gear drive - Wang Shuyan; Chen Hongwei; Zhang Xinyi; Guo Shuming; Lin Zebin; Chen Bingkui (Case Studies in Thermal Engineering)
Harmonic gear transmission is a principal mode for robot joint reducers, and an accurate steady-state temperature field model of harmonic gears is vital to improving transmission performance. In this paper, the internal relationship between instantaneous multi-tooth meshing and single-tooth continuous meshing was first investigated. Calculation methods for tooth load stress, relative speed at meshing points, and friction coefficient in multi-tooth meshing were established, and a long-axis laminated single-tooth meshing model temperature field reflecting multi-tooth meshing was constructed. Then, the temperature field of the long-axis laminated single-tooth meshing model was compared with that of the full teeth and single-tooth model in the published literature. Finally, the temperature distribution laws under different working conditions were investigated. The innovation of this paper lies in the design of the temperature field of the flexspline laminated single tooth model by integrating the harmonic transmission principle. The results show that compared with the single-tooth and full-tooth temperature field models in the current published literature, the temperature field model in this study reduces the temperature error by 29.4%–34.1 % and saves the pre-processing time by 87.5 %, enhancing the prediction accuracy and efficiency of harmonic gear temperature. This model can be utilized to assess the reliability of harmonic gears.